Pengembangan Strategi Pemasaran pada UMKM Kuliner di Kabupaten Sleman - Lukas Kopong Tukan; Ratri Paramitalaksmi (Jurnal Kabar Masyarakat, 2023)
Limited promotional media means that marketing and sales methods are still small in scope so that MSMEs cannot manage their businesses effectively and often experience delays in their development. This Community Service aims to help simplify the marketing process for culinary MSMEs, namely Siomay Indul and Warung Makan "Siderhana", which are Service Partners. The methods used in this service are: 1) interviews. 2) Observation. The results of the service that has been carried out show that the service that has been carried out has increased the skills and knowledge of the Service Partners regarding marketing strategies which also supports business development.